If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 3(3u + -1) = 16 + -1(3u + -8) Reorder the terms: 15 + 3(-1 + 3u) = 16 + -1(3u + -8) 15 + (-1 * 3 + 3u * 3) = 16 + -1(3u + -8) 15 + (-3 + 9u) = 16 + -1(3u + -8) Combine like terms: 15 + -3 = 12 12 + 9u = 16 + -1(3u + -8) Reorder the terms: 12 + 9u = 16 + -1(-8 + 3u) 12 + 9u = 16 + (-8 * -1 + 3u * -1) 12 + 9u = 16 + (8 + -3u) Combine like terms: 16 + 8 = 24 12 + 9u = 24 + -3u Solving 12 + 9u = 24 + -3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '3u' to each side of the equation. 12 + 9u + 3u = 24 + -3u + 3u Combine like terms: 9u + 3u = 12u 12 + 12u = 24 + -3u + 3u Combine like terms: -3u + 3u = 0 12 + 12u = 24 + 0 12 + 12u = 24 Add '-12' to each side of the equation. 12 + -12 + 12u = 24 + -12 Combine like terms: 12 + -12 = 0 0 + 12u = 24 + -12 12u = 24 + -12 Combine like terms: 24 + -12 = 12 12u = 12 Divide each side by '12'. u = 1 Simplifying u = 1
| 1.7-.9-.4x=-.6 | | x^3-5x^2+6x-8= | | 243=9(9x) | | n(-3)=33 | | x-6/3=1 | | 12x^2-76x+78=0 | | 28=1.8(X)+32 | | 4x=52-(x-7) | | u(9)=6 | | 2e^7x=84 | | 5(h-1)=30 | | -16t^2+400t=0 | | m(7)=10 | | 48+25+x=4x | | -3.2x-1.68=-10.00 | | (x-7)/3=1 | | (12a+2)+9= | | 10x+50=9(x+7) | | 6x+7+3x=6+2*9 | | 3(2x-1)-x=-12 | | 4(169+31)+y=21y | | x(2x-11)=-12 | | 24x=8(x-4) | | -35=5n | | 82=(2)(3.14)(65)(L) | | -20(x-2)=-30x | | 4x-8=12x-48 | | 4-3p=13 | | 15=8+7x | | 6x-16=92 | | 3.5t+4.5t+7=2t-3 | | 4(4x+5)-19= |